Movement Disorders After Exposure to Antipsychotic Drugs in Patients With Depressive Disorders - Rey, María Verónica (2018)
Objectives The aims of the study were to explore the frequency of movement disorders (MDs) in depressive patients exposed to antipsychotic drugs (APDs) and to compare it with nonexposed depressive patients and APDs-treated schizophrenic patients. Methods Four hundred fifty-two depressive patients not exposed to APDs (group A), 156 depressives exposed to APDs (group B), and 75 patients with schizophrenia on APDs (group C) were recruited. Presence of MDs was explored by the Simpson-Angus and UKU scales (Registration: NCT02409823). Results Movement disorders were observed in 5%, 9%, and 13% of patients in groups A to C, respectively (P < 0.001, χ2 for linear trend). A logistic multivariate analysis revealed that male sex (odds ratio = 2.26, 95% confidence interval = 1.13–4.49, P < 0.01), exposure to first-generation (vs second-generation) APDs (odds ratio = 5.71, 95% confidence interval = 2.08–15.66, P < 0.01), and exposure to lithium (odds ratio = 3.99, 95% confidence interval = 1.74–9.14, P < 0.01) were independently and significantly associated with MDs. Conclusions Male sex, use first-generation APDs, and exposure to lithium were associated with MDs in depression. Therefore, caution is advised with the use of these drugs in depressive patients. Prospective studies are needed to confirm these results.